2006
DOI: 10.1248/jhs.52.329
|View full text |Cite
|
Sign up to set email alerts
|

Mannooligosaccharides Blended Coffee Beverage Intake Increases the Fat Level in Feces

Abstract: Liquid coffee and milk based liquid coffee, both containing 1.0 g of mannooligosaccharides (MOS) from coffee mannan, were administered to two groups of six subjects each. The subjects consumed one or the other of the beverage everyday for two weeks. The level of fat in their excrement was subsequently analyzed. In both liquid coffee (p < 0.05, respectively) and milk based liquid coffee (p < 0.05, respectively), the concentration of the beverage containing MOS intake showed a significant decrease in comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 10 publications
0
21
1
1
Order By: Relevance
“…The previous report suggested that MOS 1.0 g/ day intake was effective in increasing the concentration of fat in feces. 4) However, the total fat utilization and the total amount of excreted fat are unknown in this study. Therefore, this experiment focused on the effect of the body fat-reducing MOS drink (containing 3.0 g of MOS per day) in humans on the total amount of excreted fat and fat utilization in the body.…”
Section: Fig 1 the Test Schedulementioning
confidence: 84%
See 1 more Smart Citation
“…The previous report suggested that MOS 1.0 g/ day intake was effective in increasing the concentration of fat in feces. 4) However, the total fat utilization and the total amount of excreted fat are unknown in this study. Therefore, this experiment focused on the effect of the body fat-reducing MOS drink (containing 3.0 g of MOS per day) in humans on the total amount of excreted fat and fat utilization in the body.…”
Section: Fig 1 the Test Schedulementioning
confidence: 84%
“…4) This result suggested that MOS intake was not only increasing the amount of total excreted fat but also inhibiting fat utilization in body. However, in order to investigate these, more accurately the clinical testing under controlled diet is required.…”
Section: Introductionmentioning
confidence: 97%
“…It is well known that catechin, [13][14][15] mannooligosaccharides, 16,17) and coffee polyphenols 18) reduce body fat; however, it is unclear whether these ingredients improve liver function. The incidence of nonalcoholic steatohepatitis (NASH) is known to be strongly associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…When mannooligosaccharides, which are also approved as FOSHU, were taken for 3 g/day, an increase of approximately 0.7-0.8 g/day of fecal fat was observed 12,13 . Therefore, to obtain an effective level of fecal fat excretion, it is necessary to increase the dosage of BOO.…”
Section: Discussionmentioning
confidence: 99%